PERANAN SARANA DAN PRASARANA PENDIDIKAN DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI MTS NEGRI 01 TULANG BAWANG KECAMATAN MENGGALA KABUPATEN TULANG BAWANG TAHUN PELAJARAN 2022/2023 - Wartini, Wartini; Nasor, M; Setyaningsih , Rina (UNISAN JURNAL, 2023)
Two main problems faced by religious people in general. On the one hand we are faced with economic, political, legal and other problems as a result of the national crisis in this field. On the other hand, we are also faced with problems between religious communities and even among the adherents of the religions themselves who have not shown close, compact and harmonious relationships. If these two problems cannot be solved immediately, it is likely that the national crisis will get worse and spread to various sectors of life. In order to anticipate these various problems, learning and education in schools must show their contribution. To improve the quality of PAI learning in schools there are many factors that influence it, one of which is the factor of educational facilities and infrastructure. The objectives to be achieved in this study are to find out the facilities and infrastructure needed to improve the quality of learning at MTs N 01 Tulang Bawang, to find out the process of the role of educational facilities and infrastructure in improving the quality of learning at MTs N 01 Tulang Bawang, and to find out the results of the improvement the quality of learning at MTs N 01 Tulang Bawang through the role of educational facilities and infrastructure. This research was conducted using descriptive qualitative research, because with the aim to describe or describe the phenomena that exist in the research location. Based on the results of the research above, it can be concluded that MTs N 01 Tulang Bawang in improving the quality of learning uses the facilities and infrastructure that are available and ready to use. This is due to the role of good educational facilities and infrastructure by school components. And the results are quite satisfying, both students, teachers and schools can feel the results with this role.